Lembaga Pemasyarakatan Kelas II A Wanita di Yogyakarta (Penekanan pada Arsitektur Bioklimatik) - Goesman, Hasma Aulia, Ir. Samsudin Raidi, M.sc (2016)
Prison is a dwelling inhabited by individuals who have one or more cases of the problem of crime, so that the individual must be stay "temporary" in the Correctional Institution. The so-called individual prisoners or detainees. Penitentiary itself is built with the aim to protect and guarantee the individual rights that are in it. With the building Penitentiary This will ultimately support the security and safety of individuals within and in the surrounding environment, especially for the local community.Yogyakarta is the capital city of the city of Yogyakarta, where the city was under the leadership of Yogyakarta. Yogyakarta is an area that has the climate and the weather was good enough to socially constructed buildings such as the Correctional Institution in order to create a building that does not seem creepy but also provide comfort to occupants who will also affect the view of the surrounding environment. Given Yogyakarta does not have Penitentiary devoted to women, the plan is deemed to be appropriate to look at the environmental conditions around the Yogyakarta area.The design concept of the physical appearance of the building exterior and interior of the building will be emphasized in linking to the climatic conditions with the daily activities of the man himself. Keywords: Woman Penitentiary Class II A, bioclimatic architecture, D.I Yogyakarta.